Pengaruh Penerapan Kurikulum Merdeka Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 1 Larantuka Tahun Pelajaran 2025/2026 - Kristina Ena Sogen; Maria Anita Titu; Maria Fatima Bongi Beribe (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to analyze the effect of the implementation of the Merdeka Curriculum on students' learning outcomes at SMA Negeri 1 Larantuka. The research employed a quantitative approach using a survey method. The study population consisted of 90 students, all of whom were included as the research sample using a saturated sampling technique. Data were collected through questionnaires to measure the implementation of the Merdeka Curriculum and documentation to obtain students' learning outcomes. Data were analyzed using descriptive statistics, prerequisite tests including normality and linearity tests, and simple linear regression analysis with the assistance of SPSS software. The results indicate that the implementation of the Merdeka Curriculum has a positive and significant effect on students' learning outcomes. This is evidenced by a significance value of 0.000 (p < 0.05) and a calculated t-value of 8.915, which is greater than the critical t-value of 1.987, leading to the acceptance of the alternative hypothesis. The coefficient of determination (R²) of 0.475 indicates that the implementation of the Merdeka Curriculum contributes 47.5% to students' learning outcomes, while the remaining 52.5% is influenced by other factors beyond the scope of this study. These findings suggest that optimizing the implementation of the Merdeka Curriculum can improve the quality of the learning process and enhance students' academic achievement.